Connexin-43 channels are a novel pathway for discharging lactate from glycolytic pancreatic ductal adenocarcinoma cells - Dovmark, T; Saccomano, M; Hulikova, A; Alves, F; Swietach, P (Springer Nature, 2017)
Glycolytic cancer cells produce large quantities of lactate which must be removed in order to sustain metabolism in the absence of oxidative phosphorylation. The only venting mechanism described to do this at an adequate rate is H+ -coupled lactate efflux on monocarboxylate transporters (MCTs). Outward MCT activity is, however, thermodynamically inhibited by extracellular acidity, a hallmark of solid tumours. This inhibition would feedback unfavourably on metabolism and growth, raising the possibility of other venting mechanisms becoming important in under-perfused tumours. We investigated connexin-assembled gap junctions as an alternative route for discharging lactate from pancreatic ductal adenocarcinoma (PDAC) cells. Diffusive coupling (calcein transmission) in vitro was high between Colo357 cells, lower yet hypoxiainducible between BxPC3 cells, and very low between MiaPaCa2 cells. Coupling correlated with expression of Cx43, a protein previously linked to late-stage disease. Evoked lactate dynamics, imaged in Colo357 spheroids using cytoplasmic pH as a read-out, indicated that lactate anions permeate gap junctions faster than highly-buffered H+ ions. At steady-state, junctional transmission of lactate (a chemical base) from the spheroid core had an alkalinizing effect on the rim, producing therein a milieu conducive for growth. Metabolite assays demonstrated that Cx43 knockdown increased cytoplasmic lactate retention in Colo357 spheroids (diameter ~150µm). MiaPaCa2 cells, which are Cx43-negative in monolayer culture, showed markedly increased Cx43-immunoreactivity at areas of invasion in orthotopic xenograft mouse models. These tissue areas were associated with chronic extracellular acidosis (as indicated by the marker LAMP2 near/at the plasmalemma) which can explain the advantage of junctional transmission over MCT in vivo. We propose that connexin43 channels are important conduits for dissipating lactate anions from glycolytic PDAC cells. Additionally, lactate entry into the better-perfused recipient cells has a favourable alkalinizing effect and supplies substrate for oxidative phosphorylation. Connexin43 is thus a novel target for influencing metabolite handling in junctionally-coupled tumours.